A Randomized Controlled Trial of the Efficacy of Expressive Writing as an Intervention for WarExposed Iraqi Adolescences in Basrah - Alshiwali, Amin Z.; Issa, Sajjad S (International Journal of Psychosocial Rehabilitation, 2020)
Expressive writing is a new psychological treatment and it is currently under study by many researchers in mental health. The aim of the present study is to test the efficacy of expressive writing as a psychological therapeutic intervention. A sample of 106 students from two intermediate schools, in Basra was included in this study and as follow: ALAshaar for girls and Al-Rashideen for boys, the data were collected during the period from 15th of November to 10th of December in 2011. Those students randomly allocated to two groups, one write in emotional way and the other write on neutral topics. Those students were assessed one week prior to the intervention and two weeks after it using the four types of questionnaires viz. Modified War Trauma Questionnaire (WTQ), Spence Children Anxiety Scale (SCAS), Birleson's Depression Self Rating Scale for Children (DSRS-C) and Children Revised Impact Events scale-8 (CRIES-8). The maximum level of effects was observed in PTSD students who did emotional expressive writing. The males were found to be more affected than the female. Similar results were obtained form the GAD study. The GAD occupied 2nd degree in the beneficial level. No significant effect was shown in Depressed students. The present research trials has beneficial outcomes on physical and psychological health. The expressive writing is not cost-effective, not time consuming, easy to administer, there is actual need to conduct further researching in the future to determine the beneficial outcomes in order to involve it in mental health therapy. In order to obtain better outcomes in prospective similar study, it is important to give more time for follow up from at least 6 months post intervention and to recruit a sufficient sample number of participants